Answer:
First one is d and second one is c
Step-by-step explanation:
(6x+7)(x-8)
(6x)(x) = 6x^2
(6x)(-8) = -48
(7)(x) = 7x
(7)(-8) = -56
Add all like terms together and you get choice d.
(w+3)(w-3)
(w)(w) = w^2
(w)(-3) = -3w
(3)(w) = 3w
(3)(-3) = -9
Add all like terms together and you get choice c
13x - y = 3 .....(1)
x - 6y = -33 ......(2)
eqn (2) × 13
13x - 78y = -429 .....(3)
(3) - (1)
13x - 78y = -429
13x - y = 3
(-). (+). (-)
_________________
- 77y = 431
_________________
-77y = 431
y = 431 ÷ -77
y = -5.5
Answer:
I think its true..................
Answer:
the ratio is 4:5
Step-by-step explanation:
1) Replace the the <em>x</em> in (5x-2y) with 2 and the <em>y</em> with 3.
2) Replace the <em>x</em><em> </em>in (x+y) with 3 and the <em>y</em> with 3.
3) 5(2) - 2(3) > 10 - 6 > 4
4) 2 + 3 = 5
5) The ratio is 4 to 5.